Cognitive effects of chemotherapy and/or cranial irradiation in adults = Kognitive Leistungsfähigkeit von Erwachsenen nach Chemo- und/oder kranieller Strahlentherapie - Welzel, Grit; Steinvorth, Sarah; Wenz, Frederik (Strahlentherapie und Onkologie, 2005)
Background: Cognitive effects after cranial radiotherapy are widely discussed, but there is growing evidence that chemotherapy may also induce changes in neuropsychological functioning. This review summarizes the published literature regarding cognitive functioning after cancer therapy in adult patients. Material and Methods: 63 reports from January 1980 to July 2003 assessing objective cognitive effects of irradiation and/or chemotherapy by neuropsychologic evaluation were analyzed. 57 studies with 3,424 patients were included for evaluation. Results: The results of this review confirm that both chemotherapy and irradiation can result in cognitive deficits. No clinically relevant differences are found for cognitive deficits, cognitive impairment rate, and single cognitive domains, when chemotherapy, cranial irradiation and combined radio- and chemotherapy were compared. Only 28 trials with 1,000 patients report quantitative data on patients with cognitive deficits after therapy. There are 44.1% (range 18-75%) of 451 patients in the chemotherapy group, 44.0% (range 29-83%) of 320 patients in the radiotherapy group, and 64.5% (range 30-100%) of 229 patients in the combined irradiation and chemotherapy group with cognitive deficits. Furthermore, cognitive functioning below average before chemo- or radiotherapy is found in subgroups of cancer patients. Conclusion: There is evidence of cognitive impairment in adult tumor patients after chemotherapy similar to effects after cranial irradiation. Cognitive functioning below average before therapy may be due to paraneoplastic effects. More prospective studies with,a Long-term follow-up using standardized neuropsychometric testing, assessment of premorbid intelligence, and suited control groups are needed.